Potentiostatic, cyclic voltammetric and pulsed electrodeposition of cadmium selenide thin films - Ahmad Wazir, Norhidayah (2010)
Cadmium selenide thin films were electrodeposited on the indium tin oxide (ITO)conducting glass substrate from an electrolyte containing of CdSO4 and SeO2 by potentiostatic (PSD), cyclic voltammeric (CVD) and pulsed lectrodeposition (PED)technique. The cyclic voltammetry experiments were also carried out to determine the range of potential for deposition of CdSe through potentiostatic and pulse techniques. Potentiostatic electrodeposition experiments have been carried out at varying deposition potential, deposition time and bath temperature. For CVD the effect of varying the number of cycle, scan rate, and deposition at different bath temperature were studied. While the effect of different pulse potential and duty cycles were investigated for PED. X-ray diffraction confirmed that polycrystalline CdSe of hexagonal structure was formed on the ITO substrate for PSD technique, while for CVD and PED technique, mixture of hexagonal and cubic CdSe phase were observed. The films exhibited n-type semiconducting behavior for PSD but p-type for CVD. Heating the sample prepared by CVD at 550°C, removes unwanted selenium element, enhanced the morphology of the film and changed the semiconducting behavior from p-type to n-type. More interesting, as deposited PED films showed both n-type and p-type behavior based on their response to the light illumination. SEM micrograph confirmed the polycrystalline nature of all deposits. In these three techniques, the photoactivity, composition, grain size and shape of the film were found to be dependent on the electrodeposition condition. CdSe thin film was successfully obtained from the mixture of 0.06 M CdSO4 and 0.005 M of SeO2 solution at potential -0.68V vs Ag/AgCl for preparation through PSD. Thicker films were formed at prolong deposition time. The PSD of CdSe was most suitable to be carried out at room temperature. Lower number of cycle and scan rate are preferable for CVD, with potential range between -1.0V to 1.0V. Smooth and well adherent samples were obtained. CVD technique produces selenium rich sample. But the excess of selenium could be eliminated by calcination at 550oC. PED produces smooth and compact films at -0.8V with 50% duty cycles. Among these three techniques, potentiostatic was found to be able to produce nearly stoichiometric of CdSe thin films. The optical absorption studies revealed that all films have direct optical band gap energy values, Eg, in the range of 1.7 to 2.0 eV.